Bone ablation using a Ho:YAG laser - Cetin Cigdem; Drusová Sandra; Hamidi Arsham; Rauter Georg; Cattin Philippe; Zam Azhar; Canbaz Ferda (Current Directions in Biomedical Engineering, 2022)
This study aimed to optimize the ablation depth and duration at a fixed energy using a Ho:YAG laser, considering fiber delivery applications. According to the measurements performed with an optical coherence tomography system, we obtained depths of about 1.4 mm with 500 mJ/pulse applied energy when moving the laser along a 1 cm line for 60 s (corresponding to ~50 pulses per position). Coupling this laser into a flexible fiber (θ= 250 μm) will be the next step for future minimal-invasive bone ablation trials. Furthermore, deeper ablation (~1.5 mm) was also achieved with different energy levels on bone samples.